An Analysis of Grammatical Errors in Indonesian-English Writing Descriptive Text Translation - Adinda Dwi Andiny; Nike Angraini; Dio Resta Permana (Departement of Mathematics Education, 2024)
This research investigated the grammatical error of students’ translation Indonesian descriptive text into English is taught to eighth-grade pupils at Tri Dharma Palembang Junior High School. This study sample was conducted using descriptive qualitative research methods. The data were collected by using documentation and test as the instrument. There would be 10 participants of this research; they are the greatest students in English in the class according to the result of try out. The research finding showed that the 0% error for run-on sentence, 1% errors for omission, 1% errors for incomplete sentence, 1% errors for word form, 1% errors for punctuation, 2% errors for addition, 3% errors for spelling, 4% errors for word order, 7% errors for verb tense, 8% errors for article, 9% errors for word choice, 13% error for singular or plural, 22% errors for capitalization, and 28% errors for meaning not clear. Based on the result of students’ translation, it showed that student made the highest error in meaning not clear which needed to practice more how to use the right word based on the context from the source language and Grammar errors were created by students due to their lack of knowledge about English part of speech. made in translating descriptive text.